Influential Factors on Consumer Purchase Intentions: Cases of Instant Noodle Products in the Hungarian Market - Nagy, Csaba Janos (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
This research investigates the factors that impact consumer purchase intention towards instant noodle products in the Hungarian market. A comprehensive literature review indicates that there are five main factors that have impact on willingness to purchase instant noodle products, which is the measurement item to purchase intention towards instant noodle products. However, the results show that there are four main factors, which are packaging (appearance), product aspect of price (product price compared to average), promotion (drive, marketing communication) and convenience (decision-making process, time spent on preparing food, time spent on shopping). The research concludes that young (less than 35), single, lower educated (elementary school, high school or vocational/associate’s degree) and below average or close to average (less than 100,000 HUF and 100,001-200,000 HUF) net earners show the highest willingness to purchase. This consumer profile is to be targeted by business professionals to enhance purchasing of instant noodle products in Hungary.